Overview of Primary Malignant Tumors Affecting the Hip - Gianakos, Arianna L.; Patel, Jay N.; Miller, Justin M.; Wittig, James C. (The Journal of Hip Surgery, 2019)
Malignancy within the hip joint can present with nonspecific symptoms such as a limp, joint stiffness, and pain. While malignant disease within the hip joint is not as common as in other areas of the body, its recognition is important, as a delay in proper diagnosis may be detrimental to patient outcomes. The authors present an overview of several malignant disease processes involving the hip joint as well as the senior author's preferred technique for endoprosthetic reconstruction in treating these conditions.
Keywords: orthopaedic oncology; tumor; malignant; sarcoma; endoprosthesis